Design and manufacturing of iris waveguide filters for satellite communication - Hicham Setti; Asmae Mimouni; Abdelwahed Tribak (Universitas Ahmad Dahlan, 2023)
We propose in this paper, two bandpass filters in waveguide technology having rectangular symmetrical discontinuities with a half-radius r, designed and operating respectively in the X-Band (9-11.5) GHz and C-Band (3.5-5.5) GHz. These filters consists of eight irises placed symmetrically respectively on standard rectangular waveguides WR90 and WR229 in which resonant irises are inserted. These irises are used to couple the sections very strongly in this filter, which allows the bandwidth to be increased and the matching to be controlled. The comparison between the numerical and electromagnetic results, which we obtained for the filters, constitutes a means of validation of computer simulation technology (CST) environment and Mician for the design of the other circuit elements in the various frequency bands. We observed excellent consistency between the simulation curves and those of the measurements. The results obtained are promising and pave the way for the use of these structures in the fields of telecommunications.